CAFF Technical Report No.16 --- Seabird Harvest in the Arctic - Arctic Council , Conservation of Arctic Flora and Fauna Working Group (caff, 2009)
Arctic Council's CAFF Working Group Technical Report No.16 - Seabird Harvest in the Arctic